Rap, langues, « québéquicité » et rapports sociaux de sexe : pratiques et expériences de rappeuses montréalaises d’origine haïtienne - Lesacher, Claire (Diversité urbaine, 2014)
Depuis les récits retraçant ses premières heures, la scène rap montréalaise apparaît particulièrement investie par des acteurs d’origine haïtienne : un fait notamment palpable à travers les textes de rap, qui présentent fréquemment des occurrences en créole haïtien. Prenant acte de cette caractéristique du rap montréalais, nous proposons une réflexion sur les enjeux de la visibilité des migrants et descendants de migrants haïtiens au sein de l’espace public québécois, à travers une focalisation sur les pratiques et expériences de rappeuses montréalaises d’origine haïtienne. Dans cette contribution, qui vise à entrevoir les processus de majoration et de minoration à l’oeuvre dans le contexte montréalais et québécois, nous envisagerons notamment la manière dont les vecteurs de différenciation impliquant ce qui relève du linguistique, de la « québéquicité » ou des rapports sociaux de sexe s’actualisent et se reproduisent dans le cadre de la médiatisation des productions artistiques.
https://doi.org/10.7202/1035426ar
Keywords: amériques; analyse de discours; approches et analyses; discipline; femmes* artistes; femmes* haitiennes; femmes* immigrantes; féminisme matérialiste; intersectionnalité; linguistique; montréal; musique; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail; écriture des femmes*; étude qualitative

Queer excursions: retheorizing binaries in language, gender, and sexuality - Zimman, Lal; Davis, Jenny L.; Raclaw, Joshua (Oxford University Press, 2014)
Across scholarship on gender and sexuality, binaries like female versus male and gay versus straight have been problematized as symbols of the stigmatization and erasure of non-normative subjects and practices. The chapters of Queer Excursions offer a series of distinct perspectives on these binaries as well as on a number of other, less immediately apparent dichotomies that nevertheless permeate the gendered and sexual lives of speakers in various contexts. Some chapters focus on the limiting or misleading qualities of binaristic analyses, while others suggest that binaries are a crucial component of social meaning within particular communities of study. Rather than simply accepting binary structures as inevitable, or discarding them from our analyses entirely based on their oppressive or reductionary qualities, this volume advocates for a retheorization of the binary that affords more complex and contextually grounded engagement with speakers’ own orientations to dichotomous systems. It is from this perspective that contributors identify a number of diverging conceptualizations of binaries—including those that are non-mutually exclusive, those that liberate in the same moment that they constrain, those that are imposed implicitly by researchers, and those that recontextualize familiar divisions with innovative meanings. With each chapter having a perspective on locally salient linguistic practices that help constitute gender and sexuality in marginalized communities, what the contributions to Queer Excursions together demonstrate is that researchers must be careful to avoid the assumption that our own preconceptions about binary social structures will be shared by the communities we study.
Donné en lecture au cours LIN2685 et POL4105, Jenny L. Davis, “More Than Just ‘Gay Indians’”: Intersecting Articulations of Two-Spirit Gender, Sexuality, and Indigenousness, pp62-80.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; pol4105; premier cycle; queer; ressource en ligne; sciences humaines; sociolinguistique; sofia; thématiques